(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the knowledge, attitudes, and practices (KAP) regarding quality improvement (QI) activities among nurses and midwives at Hue University of Medicine and Pharmacy Hospital, and to identify factors associated with these domains. Methods: A cross-sectional descriptive study was conducted among 215 nurses and midwives who had been working at the hospital for at least six months. Data were collected using a self-administered questionnaire consisting of 12 items on knowledge, 8 on attitude, and 10 on practice toward QI activities. Knowledge scores were converted to percentages, with ≥75% of the total score considered adequate. Attitude and practice were assessed using a 5-point Likert scale, with mean scores ≥3.5 considered positive or good. Data were analyzed using SPSS version 20.0, applying the Chi-square test, odds ratio (OR), and 95% confidence interval (CI), with a significance level of p<0.05. Results: The proportions of nurses and midwives with adequate knowledge, positive attitude, and good practice were 87.4%, 90.2%, and 81.4%, respectively. Years of experience were significantly associated with knowledge and practice, while knowledge level was significantly associated with practice (p<0.05). No significant associations were observed for other factors. Conclusion: Nurses and midwives generally demonstrated good knowledge, positive attitudes, and relatively high levels of practice toward quality improvement activities. Years of experience and knowledge level were associated with better practice.